2002
DOI: 10.4081/ijas.2002.35
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate improves growth performance of weaned piglets during the first period after weaning

Abstract: The purpose of the present work was to evaluate whether the addition of sodium butyrate to feed could facilitate weaning and growth response in piglets. For 56 days two groups of 20 piglets (9.2±1.4 kg LW) were fed an acidified basal diet (containing formic and lactic acid at 0.5 and 1.5 g/kg of feed, respectively) without (control group) or with sodium butyrate (SB) at 0.8 g/kg. Average daily gain (ADG), daily feed intake (DFI), feed efficiency (FE) and live weight (LW) were recorded. In the first two weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 17 publications
9
54
1
1
Order By: Relevance
“…Similarly, CCB-supplemented calves had a lower FCR than NCB calves. These findings are in agreement with those reported by Piva et al (2002) and Hill et al (2007), who included sodium butyrate in piglets' and calves' diets, respectively. Feed intake, ADG and rumen development are critical in young calves where solid DMI is often insufficient.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, CCB-supplemented calves had a lower FCR than NCB calves. These findings are in agreement with those reported by Piva et al (2002) and Hill et al (2007), who included sodium butyrate in piglets' and calves' diets, respectively. Feed intake, ADG and rumen development are critical in young calves where solid DMI is often insufficient.…”
Section: Discussionsupporting
confidence: 92%
“…Our study did not reveal an obvious change in average daily feed intake, average daily gain, and the feed/gain ratio between the sodium butyrate and control groups, but sodium butyrate exerted a significant effect on ameliorating diarrhea. Sodium butyrate has been shown to relieve diarrhea caused by weaning stress or enterohemorrhagic Escherichia coli in piglets [19][20][21]. Moreover, butyrate therapy is beneficial in patients with congenital chloride diarrhea [22,23], consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…Galfi and Bokori (1990) found that the diet containing 0.17% sodium butyrate increased the ADG and feed consumption of pigs weighing 7 kg. Piva and Morlacchini (2002) found that 800 mg/kg sodium butyrate improved growth performance of weaned piglets during the fi rst two weeks period after weaning.…”
Section: Discussionmentioning
confidence: 95%
“…Some investigators have reported that addition of sodium butyrate in diets promoted the growth of weanling pigs (Galfi and Bokori, 1990;Piva and Morlacchini, 2002). Kotunia et al (2004) found that sodium butyrate increased the small intestine development in neonatal piglets fed by artifi cial sow.…”
Section: Introductionmentioning
confidence: 99%